2019
DOI: 10.1029/2018ef000994
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Flood Vulnerability Reduction via Private Precaution

Abstract: Private precaution is an important component in contemporary flood risk management and climate adaptation. However, quantitative knowledge about vulnerability reduction via private precautionary measures is scarce and their effects are hardly considered in loss modeling and risk assessments. However, this is a prerequisite to enable temporally dynamic flood damage and risk modeling, and thus the evaluation of risk management and adaptation strategies. To quantify the average reduction in vulnerability of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 83 publications
3
33
1
Order By: Relevance
“…However, the implemented measures did not completely prevent losses during extreme fluvial floods (Table 1: Median water depth for all the events was more than 1.5 m). Since most of the property-level flood barriers were overtopped during these events (Hudson et al, 2014;Sairam et al, 2019), the implemented measures could mostly reduce the…”
Section: Hbm Structurementioning
confidence: 99%
“…However, the implemented measures did not completely prevent losses during extreme fluvial floods (Table 1: Median water depth for all the events was more than 1.5 m). Since most of the property-level flood barriers were overtopped during these events (Hudson et al, 2014;Sairam et al, 2019), the implemented measures could mostly reduce the…”
Section: Hbm Structurementioning
confidence: 99%
“…Printer-friendly version Discussion paper synthetic models rely on a description of flood damage mechanisms (Gerl et al, 2016). Some empirical flood damage models include precautionary measures as explanatory variables (see for example Kreibich et al (2017)) and can be used to estimate their mean efficacy (Sairam et al, 2019). They account for the mean effect of all measures in the sample used to produce them on flood damage.…”
Section: Interactive Commentmentioning
confidence: 99%
“…Studies have shown that private precaution can reduce loss [37,26,53,56], but implementation/uptake levels are often low and usually only rise following a flood event [36,18,32,50]. Knowledge about private precautionary measures and how to incorporate them into a flood risk management plan is scarce [38].…”
Section: Introductionmentioning
confidence: 99%